Analysis of Working of Shortwave Diathermy Machine - Deepanshu Rao (Journal of Electronic Design Engineering, 2020)
Right now, it is a restorative treatment most generally recommended for muscle and joint conditions. It utilizes a high-recurrence electric flow to invigorate heat age inside body tissues. Shortwave diathermy utilizes high recurrence electromagnetic vitality to create heat. Diathermy utilizes high-recurrence electric flow to create heat somewhere inside a focused on the tissue. It can arrive at regions as profound as two creeps underneath the surface of the skin.